Analysis of Marketing Mix on Purchase Decision of Softboned-Milkfish “Mrs. Jeni” in Malang City of East Java - Zainal Abidin; Nuddin Harahab; Boimin Boimin (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2017)
SMEs Softboned-Milkfish (called as Bandeng Presto) “Bu Jeni” is one of SMEs of fish product in Malang City. This research conducted to determine and analyze the effect of the marketing mix and marketing mix variables that have a dominant influence on purchase decisions of Softboned-Milkfish “Bu Jeni”. Research method using quantitative descriptive research. Type of data used are primary and secondary data. Determination of the number of samples using the linear time function method and the sampling technique used was accidental sampling. The method of collecting data is observations, interviews, questionnaires and documentation. Research variables used consist of independent variables including product, price, place, and promotion, as well as the dependent variable is the purchase decision. Methods of data analysis using the instrument test data, the classic assumption test, multiple linear regression analysis and hypothesis testing. The research result available to the regression equation Y = 2,695 + 0,535X1 + 0,223X2 + 0,467X3 + 0,183X4 + e. Simultaneously, the independent variables be used to real a significant effect together on the dependent variable. Partially, the independent variables have significant effect individually on the purchasing decision are product and place, while the other variables that price and promotion have no significant effect on purchasing decisions. The product strategy is the dominant variable determine the purchasing decisions.